2015
DOI: 10.14393/bj-v31n3a2015-26056
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxic activity of differents plant parts of Drimys brasiliensis miers on germination and seedling development

Abstract: ABSTRACT:The aim of this study was to evaluate the phytotoxic activity of aqueous extracts from mature leaves, stem bark and roots of Drimys brasiliensis Miers on germination and initial seedling development of two target species, Triticum aestivum L. (wheat) and Raphanus sativus L. (radish). The aqueous extract was prepared in a proportion of 10 g of plant powder, dissolved in 100 mL of distilled water, resulting in a 10% extract concentrate. Dilutions were made with distilled water to 7.5; 5.0; 2.5% and 0% (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
4
0
4
Order By: Relevance
“…Considering the presence of secondary compounds commonly reported to have allelopathic effects (Chou 2006), and the osmolality values we found for L. aurea extracts, we can argue that the inhibitory effects in seed germination found in our experiments are likely due to allelochemicals and not by osmotic pressure (Ferreira and Á quila 2000;Anese et al 2015). Other studies have reported no germination inhibition in several seed species in osmolality values above 100 mmol/kg and below -0.25 Mpa (Anese et al 2015).…”
Section: Discussionmentioning
confidence: 57%
“…Considering the presence of secondary compounds commonly reported to have allelopathic effects (Chou 2006), and the osmolality values we found for L. aurea extracts, we can argue that the inhibitory effects in seed germination found in our experiments are likely due to allelochemicals and not by osmotic pressure (Ferreira and Á quila 2000;Anese et al 2015). Other studies have reported no germination inhibition in several seed species in osmolality values above 100 mmol/kg and below -0.25 Mpa (Anese et al 2015).…”
Section: Discussionmentioning
confidence: 57%
“…Their use is of interest in weed management as they are biodegradable, have structural complexity, and a wide variety of sites of action. Additionally, they are not halogenated and are generally safer for non-target organisms [9][10][11][12]. For this purpose, several studies have aimed to identify species with phytotoxic activity [13].…”
Section: Introductionmentioning
confidence: 99%
“…When osmotic potential values show little effect amongst treatments, they probably have no effect on the germination traits evaluated [27]. erefore, the inhibitory activity of extracts observed in this present study could be attributed to the presence of phytotoxic allelochemicals in aqueous extracts of the cover crops [34].…”
Section: Discussionmentioning
confidence: 74%